Oral Bacteria of Children with Turner Syndrome - Gülcan Ünsal; Nursen Topçuoğlu; Yeliz Güven; Şükran Poyrazoğlu; Güven Külekçi; Oya Aktören (Galenos Yayinevi, 2019)
Aim:Turner syndrome (TS) is a genetic disorder caused by a numerical or structural aberration of the X chromosome, which is associated with a female phenotype. Concerning oral status, several studies have revealed that girls with TS have dental anomalies and periodontal problems. The aim of this study was to evaluate the effects of oral bacteria on caries prevalence and periodontal status in pediatric patients with TS.Materials and Methods:Twenty TS patients and 17 healthy girls were examined for cariological and periodontal status. The levels of mutans streptococci (MS), lactobacilli (LB), yeast and 10 different periodontal bacteria were determined by using culture and microarray techniques in children's stimulated saliva samples.Results:There was no difference in salivary flow rate and buffering capacity, decayed-missing-filled teeth, MS, LB, or yeast levels between the groups. Plaque index and gingival index levels were significantly higher in the Turner group and dft was significantly higher in the control group (p<0.05). As a result, microarray analysis, Prevotella intermedia, Fusobacterium nucleatum, Eikenella corrodens, Aggregatibacter actinomycetemcomitans, Actinomyces viscosus were detected at high levels in the Turner group (p<0.05).Conclusion:Besides dental and craniofacial anomalies, clinicians should be alert to the early diagnosis and treatment of periodontal problems in patients with TS.